Differences in peritoneal dialysis technique survival between patients treated with peritoneal dialysis systems from different companies. Issue 6 (14th December 2018) - Boudville, Neil; Ullah, Shahid; Clayton, Phil; Sud, Kamal; Borlace, Monique; Badve, Sunil V; Chakera, Aron; Johnson, David W
Abstract: Background: A number of peritoneal dialysis (PD) systems are available but there have been few studies comparing them. The aim of this study was to examine technique failure and patient survival between different PD company systems. Methods: The study included all patients who commenced PD between 1995 and 2014 in Australia and New Zealand. Groups were compared according to the initial PD company system that they received. The primary outcome was a composite of PD technique failure and death. Results: A total of 16 575 patients commenced PD using systems manufactured by Baxter [ n  = 13 438 (81%)], Fresenius Medical Care [ n  = 2848 (17%)] or Gambro [ n  = 289 (2%)]. Of these, 11 870 (72%) developed technique failure, including 5421 (33%) who died. The median time to technique failure or death for all patients was 625 [interquartile range (IQR) 318–1114] days: 629.5 (IQR 321–1121) days with Baxter, 620.5 (IQR 311–1069) days with Fresenius Medical Care and 538 (IQR 272–1001) days with Gambro systems (P = 0.023). There was a statistically significant increase in technique failure or mortality rates in patients on Gambro {adjusted incidence rate ratio [IRR] 1.46 [95% confidence interval (CI) 1.33–1.62]} and Fresenius [adjusted IRR 1.10 (95% CI 1.01–1.19)] systems compared with Baxter systems. No difference in patient survival was observed between the three PD systems. Conclusions: PD systems manufactured by different companies may be associated with important differences in PD technique survival. This needs to be confirmed with adequately powered, prospective randomized controlled clinical trials.